2023
DOI: 10.3390/agronomy13112807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Application Potential of Acid-Modified Cotton Straw Biochars in Alkaline Soils Based on Entropy Weight TOPSIS

Shengbao Zhu,
Jiao Liu,
Guangmu Tang
et al.

Abstract: As a good carbon source and soil conditioner, biochar is widely used in acidic soils but seldom in alkaline soils due to its high pH. In this study, cotton straw biochar was modified with five different acidic materials to obtain wood-vinegar- (WBC), monosodium-glutamate (MSG)-wastewater- (MBC), citric-acid- (CBC), phosphoric-acid- (PBC), and nitric-acid-modified biochars (NBC), and three dosages were used for each modifier. The pristine and modified biochars were characterized with scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…TOPSIS is one of many multi-objective decision-making tools [29,30] frequently employed to address multi-level and multi-objective preferences due to its wide applicability and high efficiency [31]. Numerous scholars have already used this method to solve problems in agriculture [32,33]. However, the traditional TOPSIS method relies on expert opinions to assign indicator weights, making the approach subjective.…”
Section: Entropy-weighted Topsis Methodsmentioning
confidence: 99%
“…TOPSIS is one of many multi-objective decision-making tools [29,30] frequently employed to address multi-level and multi-objective preferences due to its wide applicability and high efficiency [31]. Numerous scholars have already used this method to solve problems in agriculture [32,33]. However, the traditional TOPSIS method relies on expert opinions to assign indicator weights, making the approach subjective.…”
Section: Entropy-weighted Topsis Methodsmentioning
confidence: 99%
“…In addition to this, this paper uses the entropy-based TOPSIS method when making multi-objective decisions on multiple scenarios [38][39][40][41][42][43][44][45][46][47][48]. The methodology used has the following advantages when performing the analysis: The entropy weight method can determine the weight of the indicators by calculating the information entropy of each indicator, and then provide a basis for multi-objective evaluation.…”
Section: At the Window Performance Levelmentioning
confidence: 99%
“…For example, the following scholars use this evaluation method when making decisions about indicators. Zhu et al used the entropy-based TOPSIS method to investigate the potential of biochar application in alkaline soils; the results showed that PBDEs had the greatest potential for application [38]. Moridi et al went on to improve the bad effects of blackouts by studying the factors that affect them.…”
Section: At the Window Performance Levelmentioning
confidence: 99%
“…In the decision analysis section, this paper uses the entropy-based Topsis method [84][85][86][87][88][89][90][91][92][93] when making decisions on the optimization scheme. The method has the following advantages: The entropy weighting method can confirm the weighting information of the target indicators by analyzing the entropy value of the target indicators of each scenario, which in turn can provide a reference for the multi-objective assessment later.…”
Section: Decision Analysismentioning
confidence: 99%